(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: Pilates Method as been a popular background for almost a century and is now used worldwide as a form of fitness and holistic health because it can be tailored to individual needs and fitness levels. Lucia first advised mat exercises performed on the floor, adapting them to individual physical and temporal constraints without compromising the wider element. He later labeled a series of specialized devices, including springs and rollers, that provide resistance to develop divergent movement patterns.13 Performing exercise with medium intensity has positive effects on the maternal health. The goal of obstetric care is to provide the right conditions for a safe delivery and make it a pleasant experience. Labor pain is an unavoidable component ofchild birth whose proper management, despite the great advances in midwifery, is still one of the major challenges related to women’s health. Pregnant women should also be clinically evaluated before starting exercise to ensure there is no medical reason to stop exercising. Methods:Patients were randomly divided into two groups of 15 people in each group. In the intervention group,a Pilates exercise program was developed in collaboration with a Pilates trainer. The program was tailored to the susceptibility of pregnant women and was administered twice weekly for 8 weeks. Four tools were used in this study, including a two-part checklist, the Borg Rating of Perceived Exertion (RPE), the Visual Analogue Scale (VAS), and the McKee Childbirth Satisfaction Rating Scale. A two-section checklist was used in this study to collect the required information. Conclusion:, According to the results of this study, Pilates exercise during pregnancy is a safe method to reduce the length of the active phase and second stage of labor, reducelabor pain, and increase maternal satisfaction with the child birth process. However, Pilates exercise did not significantlyreduce the need to episiotomy and caesarean section.